Analysis of Factors Affecting The Implementation of The Integrity Zone Reviewing From The Gap Analysis of Employee Competency in Surabaya Industrial Research and Standardization Institute - Musriha; Nurul Qomari (Ekonika : Jurnal Ekonomi Universitas Kadiri, 2023)
Bureaucratic reforms launched by the government are manifested in the form of regulations or policies that must be implemented by all government agencies under the ministry. One form of this policy is the implementation of the integrity zone and the standardization of human resources as a strategic plan which is realized in the form of a competency gap analysis. This study aims to measure compliance behavior, level of complexity, clarity of organizational goals, and level of employee participation in competency gap analysis and implementation of the integrity zone. This descriptive quantitative research takes employee sampling through saturated sampling technique and data analysis is measured through path analysis. The results of the analysis prove the value of t = 2.166; p=0.034 (p<0.05), which proves that there is an effect of the level of compliance on the competency gap; t value = -0.399; p=0.691 (p>0.05) the effect of the level of program complexity on the competency gap was not proven and the value of t = 12.835; p = 0.000 (p <0.05) proves that there is an effect of the competency gap on the implementation of the integrity zone. Competency gap analysis and employee participation levels are classified as being more capable of contributing to the implementation of the integrity zone at the Surabaya Industrial Research and Standardization Institute.